Diagnosis of oral cancer using biomarkers, a non invasive proposal (International Seven Journal of Health Research, 2024)
The present study aimed to identify, through scientific literature, the use of biomarkers that help in the diagnosis of cancer in the oral cavity. This is a narrative review study with a qualitative and descriptive approach. To investigate the data, the databases of Periódicos Capes, PubMed and Sciencedirect were used, on the use of scientific articles, published during the time frame from 2019 to 2023, in Portuguese, English and Spanish, available online and free of charge, with expanded summary and in full text format. After applying filters, selecting descriptors and including review studies, meta-analysis, controlled and randomized tests, 52 articles were identified, among which 27 were from PubMed, 14 from Periódicos Capes and 11 from Science direct, in addition considering suitability, only 17 articles were registered for review. In this important study, it became evident that despite advances in the identification of tumor markers, they still do not have sufficient capacity to diagnose cancer in the oral cavity. However, it highlights its influence as an important tool for the prognosis of clinical conditions. Furthermore, it appears as a less invasive alternative, with more accessible samples such as saliva and promising results.